Globalization and Growth Prospect in Arab Countries - Alonso-Gamo, Patricia (IMF Working Papers; Working Paper, 1997)
Globalization-the intensification of international trade and finance linkages underpinned by economic liberalization and technological change-presents both challenges and opportunities to Arab countries. After reviewing this region's disappointing performance in integration and growth, this paper analyzes the empirical relationship between the two and concludes that integration is necessary if high growth rates are to be attained and the region is not to become marginalized. It then identifies the main obstacles to the integration of Arab countries into the world economy and reviews recent progress in overcoming them. On this basis, the paper derives some policy prescriptions.